If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + 12 = 5z Reorder the terms: 12 + z = 5z Solving 12 + z = 5z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-5z' to each side of the equation. 12 + z + -5z = 5z + -5z Combine like terms: z + -5z = -4z 12 + -4z = 5z + -5z Combine like terms: 5z + -5z = 0 12 + -4z = 0 Add '-12' to each side of the equation. 12 + -12 + -4z = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -4z = 0 + -12 -4z = 0 + -12 Combine like terms: 0 + -12 = -12 -4z = -12 Divide each side by '-4'. z = 3 Simplifying z = 3
| 92=x(x+4) | | a^4b^6/ab^3 | | 5/8x-51/8x=3/2 | | 9x+6(100)= | | 3q-r=7 | | 483575.32=19105.8019x^(5/2)-60446.915x | | 2=9y/4 | | 18=(4/3x)(-3/2x) | | 5/4=z/8 | | 8+6(x-3)=2-7(x-6) | | 4x*2x^2=0 | | 5/4=2/8 | | 20x-(2x-4)=40 | | (4x+7)+(2x-1)=180 | | K-7=-9 | | 3(1-2x)=2(5x-1) | | 5x+20=4x+20 | | 14+6=-4(4x-5) | | 4x-12-3x+9=2x+8 | | 2x(x-6)(3x+2)=0 | | 5a^2+3a-2=0 | | -2.3-3x-4.1-x=-3x-0.9 | | ln(3x-6)=8 | | K+12=10 | | K+10=10 | | 3x-2x+8=5x+5+3 | | -2+n=6n+22 | | -3=-15-3x | | 5a-3=a+45 | | M+22=50 | | K+18=36 | | W+39=39 |